Developing EFL religious characters and local wisdom based EFL textbook for Islamic higher education - Darmayenti Darmayenti; Besral Besral; Luli Sari Yustina (Universitas Syiah Kuala, 2021)
The development of religious characters and local wisdom in an English textbook is an effort to develop students’ English competence without ignoring their religious values and culture in English communication. The purpose of this current study is to design an EFL teaching textbook based on religious characters and local wisdom that can be appropriately used for Islamic higher education at Universitas Islam Negeri Imam Bonjol Padang, Indonesia. Research and Development type was used to design the textbook in four stages, namely, need analysis, designing textbook, try-out, and textbook revision. The observation, questionnaires, and interviews were used to collect the data. The findings revealed that textbook development resulted in eight chapters with the various themes of religious characters and local wisdom. Each chapter consists of English skills including listening, speaking, reading, writing, and grammar. The results of the textbook validations from four English language experts and learners revealed that the score was 3.53 (88.5%) within the interval of 1 to 4 and it is sorted out into a ‘strongly agree’ category. The textbook based on religious characters and local wisdom provides the students with particular challenges to respond or communicate while exploring their local cultures and practices. To find out the effectiveness of that textbook, it is recommended that an experimental study should be conducted by future researchers.